Diverse and educated workforce –requirement in the recovery context - DRĂGOIU, Codruţa Ilinca; VELCIU, Magdalena (Annals of Spiru Haret University. Economic Series, 2010)
The existence of a highly skilled workforce is a key factor to the new challenges of globalization, population growth, aging, development of new information technologies and the need for appropriate and rational use of resources. Investing in training in terms of ensuring equal opportunities is a requisite for ensuring a healthy, creative and innovative workforce, with appropriate professional skills and knowledge to produce tangible and intangible goods and services that can meet the challenges of economic recovery, being the main driver of innovation and progress. Also, a diverse workforce with varied characteristics, perspectives and ideas, is more effective in today’s society where creativity and innovation are essential.